History of the Kannada Cinema New Wave Films 1971-80 - (:unkn) unknown (My University, 2023)
"The impact of Sanskara brought several well known Kannada stories, novels and plays to the screen in 1917. The success of Vamsha Vriksha in 1972 brought new hope for the new way. The Film was based on Dr.S.L. Byrappa’s novel. Vamsha Vriksha, the film was jointly directed by Girish karnad and B.V.Karnath. This film bagged the award for best direction and regional award. In 1973, Sankalpa was directed by P.V. Ananthanagarakatti Bindu jadev. Madi Madidavaja was based on well-known novelist Basavaraja kattimani, it won the state award for second best film and best cameraman award for the year. 1973-1974 The other picture of the year ‘Kaadu’ based on Alanahali Krishna novel. Triveni’s novel Kankanamade in the same name directed by N.B.N.Prasad bagged the state award for the best film. In 1975, B.N. Karnath directed the film based on the famous novelist Dr.Shivaram Karnath Choman Dudi. It is the story of a landless agricultural lady struggling to own path in life. It won the swarna kamal award for the best feature film and Vasudev rao’s acting as Chuma was strikingly natural and won the best actress award at the national level. In kakanakote, Tabbaliyu Neenade Magane and Kanneshwara Rama the emphasis was on reals Kakanakote based on Dr. Masthi Venkatesh Iyengar popular play commercial principle and new way films principle is mixed but commercial principle dominated. Kameshwara rama based on S.K. Nagdish novel was the first Kannada film Directed by M.S. Satyu is a well known director of Hindi Films. Thabbailiyu Neenade magane a novel by B.L. Byrappa depicts the clash of values in the life of a young man who returns to his village to a foreigner wife. Chand Marutha directed by Pattabhirama Reddy was about the emergency and the following political turmoil. It was released in 1977 after the emergency ended. Chitegu chinte was the second picture directed by M.S. Satyu, master of Satire and political ridicule. The sattarical style combined with fantasies was striking. Spandana, it presented the story of a beautiful woman married to a widow the deaf and dumb child and a journey undertake. Spandana secured several awards. "
Keywords: Kannada Cinema, Kannada Movies; New Wave Films 1971-80; G.V. Iyer; M.S. Sathyu; K.P. Poornachandra Thejasvi; P. Lankesh; Kannada